The Role of Utilizing Management Audit on Human Resource Effectiveness in The Company - Imran Musa, Chalid (PT. Maju Malaqbi Makkarana, 2024)
To ensure that the human resource management function of a company or organization runs well, a human resource management audit is very important to overcome economic challenges so after all, one of the keys to a company's success lies in the quality of its human resources. The results of this literature review aim to analyze the role of management audit in human resources. The method used to write this journal article is a literature review with an explanation of findings, theories and sources from other research which are quoted from references to become the basis for conducting research that comes from thoughts that have been produced by the researchers.The results of a review of research journals overall conclude that management audits can be utilized in the effectiveness of human resources which helps achieve company goals. By increasing the effectiveness of the company to achieve its goals, the company requires a management audit. This is in accordance with the results of a review which concluded that management audit plays an important role in human resources.